2002
DOI: 10.1111/j.1572-0241.2002.06038.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling error and intraobserver variation in liver biopsy in patients with chronic HCV infection

Abstract: Liver biopsy samples taken from the right and left hepatic lobes differed in histological grading and staging in a large proportion of chronic hepatitis C virus patients; however, differences of more than one stage or grade were uncommon. A sampling error may have led to underdiagnosis of cirrhosis in 14.5% of the patients. These differences could not be attributed to intraobserver variation, which appeared to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
442
1
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,839 publications
(482 citation statements)
references
References 25 publications
3
442
1
16
Order By: Relevance
“…Conflicting results have been reported in humans about the distribution of fibrosis and inflammation between lobes. Whereas some studies have reported substantial variation in fibrosis6 and inflammation12, others have shown minimal or no significant differences between lobes 13, 14, 15. However, the population in this study was not selected for clinical suspicion of liver disease, and the clinical significance of the inflammation and fibrosis in these patients unclear.…”
Section: Discussionmentioning
confidence: 83%
“…Conflicting results have been reported in humans about the distribution of fibrosis and inflammation between lobes. Whereas some studies have reported substantial variation in fibrosis6 and inflammation12, others have shown minimal or no significant differences between lobes 13, 14, 15. However, the population in this study was not selected for clinical suspicion of liver disease, and the clinical significance of the inflammation and fibrosis in these patients unclear.…”
Section: Discussionmentioning
confidence: 83%
“…Autopsy and laparoscopy studies have demonstrated that cirrhosis is missed on a single blind liver biopsy in between 10-30% of cases. 4,5 The intra-and inter-observer variability may range from 15% to as high as 33% for determining fibrosis stage. 5 The attempts to find reliable non-invasive markers of liver fibrosis have recently increased dramatically as a result of the evolving novel therapies for hepatitis C and B.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The intra-and inter-observer variability may range from 15% to as high as 33% for determining fibrosis stage. 5 The attempts to find reliable non-invasive markers of liver fibrosis have recently increased dramatically as a result of the evolving novel therapies for hepatitis C and B. 6,7 By analogy, a considerable interest has arisen in extending this work into the field of non-alcoholic fatty liver disease (NAFLD) because of its increased prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the limitations of needle liver biopsy with respect to sampling error and interobserver variation are well described, highlighting the need for further testing strategies. 1,2 Our deeper understanding of the mechanisms of fibrosis has led to the identification of many potential markers of fibrosis, which appear capable of identifying early and advanced hepatic fibrosis. 3,4 Standard cross-sectional imaging studies will only identify or exclude advanced fibrosis.…”
mentioning
confidence: 99%